In vitro Cytotoxicity and Genotoxicity/Antigenotoxicity Evaluation of Encapsulated Black Garlic Extracts on A549 Cells - Aydemir, Çiğdem İnci; Temiztürk, Hatice Elif; Taner, Gökçe (Sağlık Bilimleri Üniversitesi, 2024)
Objectives: Black garlic is produced by fermenting fresh garlic under controlled temperature and humidity conditions for an extended period. Due to its sweeter taste and lack of pungent odor compared to fresh garlic, black garlic is easier to consume. Moreover, the increase in bioactive compounds such as polyphenols and flavonoids during fermentation has sparked interest in studying the health effects of black garlic. It is known that different fermentation and extraction methods can lead to variations in biological activities. Therefore, analyzing the effectiveness of black garlic processed by different methods is of critical importance. In our study, we investigated the cytotoxic, genotoxic, and antigenotoxic effects of different concentrations of encapsulated black garlic capsule extract (BGC) on lung cancer cells. Methods: The A549 cell line was used to investigate the effects of BGC. Cells treated with BGC at different concentrations (10, 25, 50, 100, 125, 250, 500, and 1000 µg/mL) for 24 hours were subjected to MTT and NRU assays to examine the cytotoxic effects. Alkaline comet assay was performed to investigate genotoxic and antigenotoxic effects. For antigenotoxicity analysis, cells pretreated with BGC were exposed to H2O2 to explore the protective effects of BGC. Results: According to the MTT results, cell viability remained at 90% even at concentrations higher than 125 µg/mL. However, in the NRU analysis, viability decreased to less than 70% at concentrations ranging from 50 µg/mL. Comet assay results revealed significant increases in tail length and tail intensity at different concentrations (specifically, at 250 µg/mL and above and at 50 µg/mL and 100 µg/mL, respectively). However, tail moments did not show any significant differences at any concentration. Additionally, BGC significantly reduced H2O2-induced DNA damage. Conclusions: Our research demonstrated that BGC reduces the viability of lung cancer cells and can have genotoxic effects. Additionally, its protective effect against oxidative damage was shown at the DNA level. Based on these data, further research can be conducted on the use of BGC against cancer.
Keywords: Clinical Sciences (Other); Klinik Tıp Bilimleri (Diğer)